Enhancing Arabic Speaking Skills in Pesantren Khairul Ummah Riau Through Direct Instruction: Implications for Educational Management - Erva Nurvarida; Rabiatul Hadawiyah; Neli Asmaniah; Aminudin (Al-Qalam Institue, 2025)
The role of educators in teaching a foreign language requires careful consideration, particularly in selecting effective teaching methods. This study aims to describe the implementation of the direct method in teaching Arabic speaking skills (maharah al-kalam) and its effect on improving the Arabic language program at Pesantren Khairul Ummah Putri Riau. The study employs a qualitative descriptive approach, with female students of the pesantren as informants. Data were collected using triangulated techniques, including interviews, observations, and document analysis. The findings indicate that applying the direct method in teaching speaking skills significantly enhances students’ oral proficiency and contributes to the overall improvement of the Arabic language program. The study highlights the necessity for educators’ creativity and pedagogical skills in designing effective speaking activities, as well as the importance of collaboration between teachers and students. These results imply that integrating management practices in educational planning and classroom organization can optimize language learning outcomes. By combining effective teaching methods with sound educational management, pesantren programs can achieve higher levels of learner engagement, skill acquisition, and program efficiency.